Study of hydrogen isotopes behavior in tungsten by a multi trapping macroscopic rate equation model. (8th January 2016) - Hodille, E A; Ferro, Y; Fernandez, N; Becquart, C S; Angot, T; Layet, J M; Bisson, R; Grisolia, C
Abstract: Density functional theory (DFT) studies show that in tungsten a mono vacancy can contain up to six hydrogen isotopes (HIs) at 300 K with detrapping energies varying with the number of HIs in the vacancy. Using these predictions, a multi trapping rate equation model has been built and used to model thermal desorption spectrometry (TDS) experiments performed on single crystal tungsten after deuterium ions implantation. Detrapping energies obtained from the model to adjust temperature of TDS spectrum observed experimentally are in good agreement with DFT values within a deviation below 10%. The desorption spectrum as well as the diffusion of deuterium in the bulk are rationalized in light of the model results.